2015
DOI: 10.5194/acp-15-2119-2015
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the vertical distribution of bromine monoxide in the lower troposphere on meteorological factors such as wind speed and stability

Abstract: Abstract. Multiple axis differential absorption spectroscopy (MAX-DOAS) measurements of bromine monoxide (BrO) probed the vertical structure of halogen activation events during March–May 2012 at Barrow, Alaska. An analysis of the BrO averaging kernels and degrees of freedom obtained by optimal-estimation-based inversions from raw MAX-DOAS measurements reveals the information is best represented by reducing the retrieved BrO profile to two quantities: the integrated column from the surface through 200 m (VCD200… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
144
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(173 citation statements)
references
References 67 publications
18
144
1
Order By: Relevance
“…Since the kinetic calculations used herein are based on observations performed under low wind conditions, these budgets may be considered as representative of the surroundings of each station. Figure 12 indicates that, in agreement with Peterson et al (2015), the presence of reactive bromine at both stations do not only correspond to advected bromine-enriched air masses or blowing snow. As expected from previous polar studies (e.g., Simpson et al, 2007 35 and references therein) and shown in Fig.…”
Section: Brox In Antarcticasupporting
confidence: 63%
See 3 more Smart Citations
“…Since the kinetic calculations used herein are based on observations performed under low wind conditions, these budgets may be considered as representative of the surroundings of each station. Figure 12 indicates that, in agreement with Peterson et al (2015), the presence of reactive bromine at both stations do not only correspond to advected bromine-enriched air masses or blowing snow. As expected from previous polar studies (e.g., Simpson et al, 2007 35 and references therein) and shown in Fig.…”
Section: Brox In Antarcticasupporting
confidence: 63%
“…For details on sources, sinks and historical background, the reader is kindly referred to the compendium works of e.g. Simpson et al (2007), Steffen et al (2008), Ariya et al (2015) and Simpson et al (2015) and references therein.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The meteorological satellites observe the surface of the earth and the atmosphere from outer space [3] [4]. They are characterized by high observational areas, wide observation areas and high frequency of observation [5].…”
mentioning
confidence: 99%